Blood biomarkers of secondary outcomes following concussion: A systematic review - Swaney, Ella E. K.; Cai, Tengyi; Seal, Marc L.; Ignjatovic, Vera (Frontiers in Neurology, 2023)
Blood biomarkers have been identified as an alternative of complementary prognostic tool for secondary outcomes following concussion. This systematic review aimed to summarize the literature on blood biomarkers of secondary outcomes following concussion in both pediatric and adult cohorts. A literature search of Embase, Medline and PubMed was conducted. Two reviewers independently assessed retrieved studies to determine inclusion in systematic review synthesis. A total of 1771 unique studies were retrieved, 58 of which were included in the final synthesis. S100B, GFAP and tau were identified as being associated with secondary outcomes following concussion. However, the validation of these biomarkers has been largely limited by heterogeneous study cohorts and definitions of concussion and mTBI, presenting a hurdle for translation of these markers into clinical practice. Additionally, only 17% of studies were performed in a solely pediatric setting. Adult markers are not appropriate for children, therefore pediatrics specific markers of secondary outcomes following concussion present the biggest gap in this field.